2021
DOI: 10.1108/ijoem-05-2021-0791
|View full text |Cite
|
Sign up to set email alerts
|

The impact of board composition and ownership structure on dividend payout policy: evidence from Saudi Arabia

Abstract: PurposeThis study examines the impact of board composition and ownership structure variables on dividend payout policy in Saudi Arabian firms. In particular, it aims to determine the effect of board size, independence and meeting frequency, in addition to chief executive officer (CEO) duality, and state, institutional, managerial, family, and foreign ownership on both the propensity to pay dividends and dividend per share for Saudi-listed firms over the period 2016–2019.Design/methodology/approachThe paper cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 83 publications
(196 reference statements)
6
49
0
3
Order By: Relevance
“…Huang and Paul (2017) have found that institutional-investors prefer investing in dividend-paying firms. Similar results are also reported by Guo and Ni (2008)—for US; Fairchild et al (2014) and Thanatawee (2013)—for Thailand; Boshnak (2021)—for Saudi Arabia; Bataineh (2021)—for Jordon; Thi et al (2019)—for Vietnam; and Manos (2003)—for India. Huang and Paul (2017) further corroborate their findings by depicting that the level of payout preference also depends on the company’s growth opportunities.…”
Section: Literature Review and Hypotheses Formulationsupporting
confidence: 81%
See 2 more Smart Citations
“…Huang and Paul (2017) have found that institutional-investors prefer investing in dividend-paying firms. Similar results are also reported by Guo and Ni (2008)—for US; Fairchild et al (2014) and Thanatawee (2013)—for Thailand; Boshnak (2021)—for Saudi Arabia; Bataineh (2021)—for Jordon; Thi et al (2019)—for Vietnam; and Manos (2003)—for India. Huang and Paul (2017) further corroborate their findings by depicting that the level of payout preference also depends on the company’s growth opportunities.…”
Section: Literature Review and Hypotheses Formulationsupporting
confidence: 81%
“…Boshnak (2021) has examined the corporate-governance impact and the impact of ownership structure on dividend-policy of the Saudi listed companies. For ownership structure variables, the study exhibits that INS associates positively to both the tendency to pay dividends and dividend per share (DPS).…”
Section: Literature Review and Hypotheses Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Dewan direksi yang menentukan apakah perusahaan akan membayar dividen dan menentukan tingkat dividen yang akan dibayarkan kepada investor. Keputusan ini dipengaruhi oleh struktur kepemilikan sebagai tata kelola perusahaan, yang memisahkan antara kepemilikan institusi, investor retail, manajer, pemerintah, dan apakah kepemilikan terkonsentrasi atau tersebar (Boshnak, 2021). Kebijakan Dividen merupakan isu yang telah lama menjadi polemik bagi perusahaan di berbagai negara berkembang.…”
Section: Pendahuluanunclassified
“…Penelitian tersebut menemukan hasil board size memiliki pengaruh positif dan signifikan terhadap DPR, board gender diversity berpengaruh negatif terhadap DPR, financial leverage berpengaruh negatif dan signifikan terhadap DPR, dan ROA memiliki pengaruh positif dan signifikan terhadap DPR. (Boshnak, 2021) meneliti dengan pembahasan yang sejenis, yaitu mengenai pengaruh board size, struktur kepemilikan perusahaan, rapat dewan, dewan independen, profitabilitas, firm age, firm size dan financial leverage terhadap kebijakan pembayaran dividen, menemukan hasil bahwa struktur kepemilikan perusahaan, rapat dewan, profitabilitas, dan firm age menunjukkan adanya pengaruh yang positif terhadap kebijakan dividen. Sementar itu, board size, dewan independen, firm size, dan financial leverage berpengaruh negatif terhadap kebijakan pembayaran dividen.…”
Section: Kajian Teoriunclassified